Hydropneumothorax Secondary to Community-Acquired Pneumonia with Broncholith: A Case Report - Fikri Wahyudi; Rijal Dwika Saputra (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Community-acquired pneumonia (CAP) is a common respiratory infection that can lead to serious complications, including hydropneumothorax, a condition characterized by the presence of both air and fluid in the pleural cavity. Case presentation: We present the case of a 76-year-old male who presented to the emergency department with a one-week history of shortness of breath, dry cough, and low-grade fever. He had no prior surgeries, history of tuberculosis, comorbid conditions, or significant pulmonary diseases. Physical examination revealed crackles, decreased breath sounds on auscultation, and hyperresonance on percussion of the right hemithorax. Laboratory investigations demonstrated leukocytosis and neutrophilia. Chest radiography showed consolidation consistent with pneumonia, and subsequent computed tomography (CT) confirmed the diagnosis of right hydropneumothorax with pleural effusion and a broncholith in the right basal lobar bronchus. The patient was treated with intravenous antibiotics and underwent water seal drainage (WSD). He made a full recovery and was discharged home. Conclusion: This case highlights the importance of considering hydropneumothorax as a potential complication of CAP, even in patients without significant comorbidities. Prompt diagnosis and management, including drainage and antibiotics, are crucial for a favorable outcome.